Presentations, Complications, and Challenges Encountered During Management of Type 1 Diabetes in Egyptian Children During COVID-19 Pandemic: A Single-Center Experience - Abdou, Marise; Hassan, Mona M.; Hassanein, Samah A.; Elsebaie, Eman H.; Shamma, Radwa A. (Frontiers in Endocrinology, 2022)
Background: COVID 19 pandemic was associated with many challenges during management of children and adolescents with Type 1 diabetes (T1D). The fear of infection and the lockdown measures resulted in delayed, more severe presentation. Objectives: This study aimed at reporting the frequency and severity of diabetic ketoacidosis (DKA) and the rate of DKA complications in children with diabetes who presented to the Emergency Unit during COVID 19 pandemic and to compare the data collected from COVID waves 1 and 2 with that of Pre-COVID period and finally to describe the challenges encountered during management. Methods: This cross-sectional study included all children and adolescents with T1D who presented to the Emergency Department at Abo ELRish Children’s Hospital, Cairo University during COVID wave 1 & 2. It also included data collected from Pre-COVID period. Demographic and clinical data, investigations and management details were collected from patients’ medical records. Results: Three hundred twenty-four Egyptian children and adolescents diagnosed with T1D were recruited. One hundred forty patients (43.2 %) presented with severe DKA. Around 66 % were newly diagnosed with T1D. Participants presented with manifestations suggestive of COVID19 such as fever (29.5%), respiratory manifestations (7.2%) and gastrointestinal symptoms (14.7%). Thirty-seven patients were tested for SARS-COV-2 infection using nasopharyngeal swab, four were positive. Around 18% developed hypokalemia during management. On comparing this data with data from previous years, it was observed that during COVID waves 1 and 2, there was a significant increase in the number of newly diagnosed cases with more severe DKA at presentation and higher incidence of development of hypokalemia. Conclusion: During COVID waves 1 and 2, there was an increase in the incidence of newly diagnosed cases as compared with Pre-COVID period. Patients presented with more severe DKA probably due to more delayed presentation. The incidence of development of Hypokalemia was significantly higher. The severity of DKA was associated with longer ICU admission. Further studies are required to establish a definitive link between COVID 19 pandemic and severity of presentation.